The application of Health Technology Assessment to health apps: what is the evidence?. (30th September 2020) - de Waure, C; Giacchetta, I; Violi, S; Martini, C; Favaretti, C
Abstract: Background: In the last years, many health apps have been developed to support citizens' and patients' health management. Nevertheless, a thorough evaluation is necessary to support the decision to incorporate them into healthcare systems. Health technology assessment (HTA) could be considered a valid evaluation tool allowing considering different stakeholders' perspectives. This research aimed to look for studies that applied HTA to health apps and to analyze feasibility and limits of HTA in this field. Methods: A systematic review was performed considering three databases, namely PubMed, Web of Science (WoS) and University of York-Centre for Reviews and Dissemination database. Being the topic of health app assessment new, articles were considered eligible if they assessed at least two of the domains of the HTA core model suggested by the European network for Health Technology Assessment (EUnetHTA). Furthermore, only articles published in English in the last 5 years were considered. Results: A total of 850 articles were found: 383 articles from PubMed, 462 from WoS and 5 from York. After removing duplicates, 708 articles remained and 43 were eventually included after the screening process. Seven articles were focused on apps used by healthcare professionals, while 36 dealt with apps aimed to support patients. None of the papers explicitly mentioned HTA as assessment tool. Indeed, not all the domains of the HTA core model were assessed in any article. Apps' technical description, clinical effectiveness and social aspects were the domains considered more often. On the contrary, costs and economic evaluation was clearly faced by one article only. Conclusions: Even though the scientific literature on health apps is growing, the adoption of standardized methods for their evaluation, such as HTA, is still scant. This might be due to peculiarities of health apps and points out the importance of adapting existing methods in order to let a thorough assessment possible.